2004
DOI: 10.1007/s00011-004-1246-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal anti-histamine H 2 receptor antibodies detect differential expression of H 2 receptor protein in primary vascular cell types

Abstract: We conclude that the antibodies generated against the extra-cellular domain of the H2 receptor are specific and can be utilized to detect and quantify H2 receptor expression. Furthermore, the significant differences in H2 receptor expression in different vascular cell types might play a critical role in defining histamine induced cellular responses during physiological or pathophysiological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…In the case of His, activation of H 1 receptors in HUA smooth muscle induces contraction by activation of phospholipase C and increase in IP 3 levels (Hawley et al 1995). The expression of H 2 receptors in human umbilical smooth muscle was also reported by Schneider et al (Schneider et al 2004). The activation of this receptor stimulates adenylyl cyclase activity producing an increase in cyclic AMP and relaxation.…”
Section: Discussionsupporting
confidence: 57%
“…In the case of His, activation of H 1 receptors in HUA smooth muscle induces contraction by activation of phospholipase C and increase in IP 3 levels (Hawley et al 1995). The expression of H 2 receptors in human umbilical smooth muscle was also reported by Schneider et al (Schneider et al 2004). The activation of this receptor stimulates adenylyl cyclase activity producing an increase in cyclic AMP and relaxation.…”
Section: Discussionsupporting
confidence: 57%
“…This receptor, coupled to G q protein, activates the PLC/IP 3 signalling cascade, leading to an increase in intracellular Ca 2+ levels and consequent contraction [40,41,42]. Schneider et al (2004) also reported the expression of the H 2 receptor in HUA smooth muscle [43]. This receptor, coupled to G s protein, stimulates adenyl cyclase, leading to an increase in cAMP levels and consequent relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular responses to histamine are mediated through H 1 and H 2 receptor subtypes (12), and the dissected mesenteric arteries contained both histamine H 1 and H 2 receptor mRNA (data not shown). Histamine H 2 receptors are present in cultured smooth muscle cells (28). In human radial and internal thoracic arteries, histamine evokes constriction and its concentration-response curve is shifted to the right by H 2 receptor antagonists (5).…”
Section: Discussionmentioning
confidence: 99%